2020
DOI: 10.1039/d0nr06138g
|View full text |Cite
|
Sign up to set email alerts
|

2D layered all-inorganic halide perovskites: recent trends in their structure, synthesis and properties

Abstract: Recently, halide perovskites have appeared as a superior class of materials for diverse applications, mainly in optoelectronics and photovoltaics. Perovskite halides are broadly classified as hybrid organic-inorganic and all-inorganic analogues...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 185 publications
0
35
0
Order By: Relevance
“…Dimensionality of this material is defined by the linkage of the octahedral units [PbX 6 ] 4− forming layers, chains and isolated units for CsPbX 3 and Cs 4 PbX 6 while in case of Cs 2 PbX 5 breaking of corner sharing [PbX 6 ] 4− take place forming [PbX 8 ] 6− . [39] Connectivity of the [PbX 6 ] 4− octahedra is of manifolds, varying from corner‐sharing to face‐sharing to edge‐sharing. If the octahedral units are isolated, it would correspond to 0D, while an arrangement of complete corner sharing octahedral would be a 3D perovskite.…”
Section: Mechanism Of Stokes Shift In Cspbx 3 Systemmentioning
confidence: 99%
“…Dimensionality of this material is defined by the linkage of the octahedral units [PbX 6 ] 4− forming layers, chains and isolated units for CsPbX 3 and Cs 4 PbX 6 while in case of Cs 2 PbX 5 breaking of corner sharing [PbX 6 ] 4− take place forming [PbX 8 ] 6− . [39] Connectivity of the [PbX 6 ] 4− octahedra is of manifolds, varying from corner‐sharing to face‐sharing to edge‐sharing. If the octahedral units are isolated, it would correspond to 0D, while an arrangement of complete corner sharing octahedral would be a 3D perovskite.…”
Section: Mechanism Of Stokes Shift In Cspbx 3 Systemmentioning
confidence: 99%
“…In fact, atomic bonding in most materials is anharmonic with various strengths of anharmonicity 48–55 . Strong anharmonicity causes intrinsic phonon scattering due to Umklapp processes (U‐processes) and determines the intrinsically low κ lat in materials with multidimensional crystal structures 28,29,34,51,56–62 …”
Section: Introductionmentioning
confidence: 99%
“…McCall [98], Copyright 2018 American Chemical Society gaps, respectively. The single crystals of Cs 3 Bi 2 I 9 , Cs 3 Sb 2 I 9 and Rb 3 Sb 2 I 9 displayed weak PL emission in the range of 1.58-2.2 eV with a line width of 315-403 meV, whereas no emission was evidenced for Rb 3 Bi 2 I 9 at room temperature and even at 15 K. The low-temperature PL study revealed several overlapping peaks in the specified range for Cs 3 Bi 2 I 9 at 13 K. Conversely, the PL study of Cs 3 Sb 2 I 9 and Rb 3 Sb 2 I 9 revealed a broad near band-edge emission at 1.92 eV and a broad skewed peak at 1.96 eV, respectively, at 13 K. The phonon-assisted recombination of the self-trapped excitons (STEs) was responsible for the broad emission in these materials [70,100].…”
Section: Optical Absorption and Photoluminescence Propertiesmentioning
confidence: 98%